A Self-Assessment Instrument for Early Childhood Teachers: Construct Validity and Reliability Analysis - Christianti, Martha; Harun; Nur Hayati; Oktaviani Maharani; Nazaludin Nur Rahmat; Apry Aditya Saputra; Triandi Aprilio (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Early childhood education teachers in Indonesia often lack standardized tools to assess their pedagogical and professional competence. This study aims to develop and validate a reliable self-evaluation instrument by identifying key competency dimensions to support early childhood teachers in reflecting on their professional practices. The instrument consists of 39 items encompassing seven competency dimensions: evaluation and reflection skills, holistic educational approach, curriculum mastery, learning activity design, professionalism, technology integration, and communication. Data were collected using a 4-point Likert scale from 276 respondents for exploratory factor analysis (EFA) and 978 respondents for confirmatory factor analysis (CFA). EFA was used to identify the instrument's underlying factor structure, while CFA tested the model's fit with empirical data. The EFA results indicate that seven factors with eigenvalues greater than 1 were extracted, explaining 60.378% of the total variance across the 39 items. CFA results confirm that the conceptual model aligns with empirical data, with all standardized loading factors found to be significant. Construct reliability, measured using Composite Reliability (CR), shows that four of the seven dimensions have satisfactory reliability (CR > 0.70), while the remaining three dimensions demonstrate moderate reliability. This study contributes to early childhood education by presenting a validated and reliable self-assessment instrument to measure early childhood teachers’ pedagogical and professional competence. The instrument supports teachers in reflecting on their teaching practices and promotes ongoing professional development. It also offers a foundational tool for policymakers and institutions to improve teacher quality. Future research can examine its applicability in various educational contexts and evaluate its effectiveness in guiding targeted development programs.